Emotional intelligence and its relationship to the quality of life among university students (Journal of the College of Basic Education, 2023)
Knowing one's emotional intelligence gives him the opportunity to place himself alongside others with whom he naturally identifiesAnd search for works that suit him and understand the things that make an individual incompatible with some people or with some works and learnWays to deal with natural hardships, understand some of the specific things that cause stress, and learn ways to become an individualFeeling more at peace.Personal and professional quality is essential for young people starting their own business; Some classify itResearchers need key abilities, skills, and attributes that branch out into other sub-categories, such as: vision; The initiative; common sense The need for achievement.the need for independence and the tendency to take a reasonable amount of risk; take responsibility; This is in addition to my communication skills and confidenceby breath; self awareness; motivation towards learning in a variety of ways; persuasion skills; stamina and tolerance; and planningdecision-making skills and the ability to synthesize; listening skills; Gathering and analyzing information as well as solving skillsthe problems; take notes; project management; team management and time management; And the ability to create.